FREQUENCY OF CHRONIC COMMON SOMATIC PATHOLOGY IN THE WORKERS OF MAIN PROFESSIONS OF COAL MINING ENTERPRISES OF THE SOUTH OF KUZBASS - Коротенко, Ольга Юрьевна; Филимонов, Егор Сергеевич; Блажина, Ольга Николаевна; Уланова, Евгения Викторовна (Medicine in Kuzbass, 2019)
Subject of the study. 1563 workers of the mines in the South of Kuzbass were examined: men aged from 22 to 60 years who were divided into 2 professional groups depending on the classes of danger and harmfulness, on subgroups by age (from 22 to 30 years, from 31 to 40 years, more than 40 years) and work experience (up to 10 years, from 11 to 20 years, over 20 years). Objective – to assess the frequency of chronic common somatic pathology in coal miners. Methods of the study. The data of the occupational history, working conditions, health indicators according to periodic medical examinations were analyzed. The codes of chronic common somatic diseases in accordance with ICD-10, including the date of the established diagnosis, were obtained during the processing of outpatient cards. Main results. In the structure of common somatic diseases the leading places corresponded to three main nosological directions: in the first group with hazard class 3.3 and 3.4 diseases of the musculoskeletal system and connective tissue (36.5 %), of the nervous system (24.4 %), diseases of the circulatory system (16.9 %) prevailed; in the group with hazard class 3.2 and 3.1 there were diseases of the circulatory system (27 %), diseases of the musculoskeletal system and connective tissue (25.5 %), diseases of the nervous system (11.6 %). The subjects with work experience up to 10 years and from 11 to 20 years had a higher percentage of the frequency of somatic pathology in the first group compared to the workers of the second group. Among the surveyed subjects engaged in the workplace with higher classes of danger and harmfulness, a large proportion of common somatic diseases among the respondents of older age groups was revealed. Scope of their application. These results are applicable in the practice of occupational therapists, therapists, cardiologists, neurologists. Conclusions. In our research, we studied the frequency of chronic common somatic diseases in coal miners of the main professions. The great prevalence of somatic pathology in the group of miners with a high class of danger and harmfulness has been established.